Produção de aromas químicos na empresa Capuani do Brasil Ltda - Chastrette, Clément Pierre (2015)
This document relates of the main activities of the chemical engineering’s student Clément Pierre Chastrette during his internship which was realized in the firm Capuani do Brasil Ltda., located in Tietê – SP, from the 03/08/2015 to 30/11/2015. The trainee has carried out in the flavors’ production and accomplished his missions focusing on the quality and the good manufacturing practices. The internship included the aspects of respect of the environment, which has a great importance in the professional and personal apprenticeship for the formation of the chemical engineer. Industrial production of flavors, improvement of a distillation column’s layout, and research on flavors were the tasks of the trainee. Unfortunately, this document will not relate on the research done during the internship for the conservation of trade secret.